Chromosomal and environmental contributions to sex differences in the vulnerability to neurological and neuropsychiatric disorders: Implications for therapeutic interventions. (December 2022) - Pallier, Patrick N.; Ferrara, Maria; Romagnolo, Francesca; Ferretti, Maria Teresa; Soreq, Hermona; Cerase, Andrea
Abstract: Neurological and neuropsychiatric disorders affect men and women differently. Multiple sclerosis, Alzheimer's disease, anxiety disorders, depression, meningiomas and late-onset schizophrenia affect women more frequently than men. By contrast, Parkinson's disease, autism spectrum condition, attention-deficit hyperactivity disorder, Tourette's syndrome, amyotrophic lateral sclerosis and early-onset schizophrenia are more prevalent in men. Women have been historically under-recruited or excluded from clinical trials, and most basic research uses male rodent cells or animals as disease models, rarely studying both sexes and factoring sex as a potential source of variation, resulting in a poor understanding of the underlying biological reasons for sex and gender differences in the development of such diseases. Putative pathophysiological contributors include hormones and epigenetics regulators but additional biological and non-biological influences may be at play. We review here the evidence for the underpinning role of the sex chromosome complement, X chromosome inactivation, and environmental and epigenetic regulators in sex differences in the vulnerability to brain disease. We conclude that there is a pressing need for a better understanding of the genetic, epigenetic and environmental mechanisms sustaining sex differences in such diseases, which is critical for developing a precision medicine approach based on sex-tailored prevention and treatment.